Bringing Translation into the Canon : The Importance of the Folhetim in Translation Studies in Brazil - Milton, John (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
The focus of this article is on the important role of the Folhetim, the Cultural Supplement of the São Paulo newspaper, the Folha de São Paulo, in the growth of Translation Studies in Brazil in the 1980s and early 1990s. I propose that the Folhetim was central to the formation of the discipline, which only later, in the 1990s, began at university level. Central to the Folhetim are Haroldo and Augusto de Campos, much of whose work was published in the supplement. And perhaps the fact that the cultural supplement of a newspaper, and not academic journals, first published much of their work resulted in a much greater visibility for literary translation in Brazil.